The Dispersion of Senses about the “Anti-Homophobia Law” in Brazilian Newspapers: An Investigation Based on Membership Categorization Analysis - Depiné Alves Guimarães, Juliana (Brazilian journalism research, 2018)
In 2001, Iara Bernardi, then Representative of the Labor Party (Partido dos Trabalhadores) in São Paulo, proposed Bill 122, known as the “anti-homophobia law”, with the goal of including discrimination against sexual orientation or gender identity as identified in the criminal code (in particular, Law 7716 from 1989, also known as the Racism Law). This paper presents some of the conclusions I reached while doing my PhD research investigating the journalistic coverage of Bill 122 between 2001 and 2015; the year it was filed away. This investigation was conducted based on the methodological tools from the Membership Categorization Analysis (MCA). The result of the analysis brought four analytical patterns to light, which encompass the categorizations of membership used in journalistic discourses during that period for issues such as LGBT, Bill 122 itself, homosexuality and Brazilian institutions, in which, Brazil, the Congress and the State are categorized. For the purposes of the analysis, we applied the term “conservative” to the categorizations of Congress. Em 2001, a então deputada Iara Bernardi (PT-SP) propôs, na Câmara dos Deputados, o Projeto de Lei da Câmara 122 (PLC 122), conhecido como “lei anti-homofobia”, com o objetivo de ampliar a Lei do Crime Racial (7716⁄89) para incluir a discriminação por orientação sexual ou identidade de gênero. Este artigo apresenta um recorte das conclusões de minha tese de doutorado, que investigou a cobertura jornalística sobre o PLC 122, entre 2001 e 2015, quando o Projeto foi arquivado, com base na Análise de Categorização de Pertencimento (Membership Categorization Analysis). Em primeiro lugar, o artigo apresenta um panorama dos quatro padrões analíticos evidenciados pelo estudo, que englobam as categorizações de pertencimento utilizadas no âmbito dos discursos jornalísticos no período, acerca dos sujeitos LGBT, do projeto de lei em si, da prática homossexual e das instituições brasileiras, em que o Brasil, o Congresso Nacional e o Estado são categorizados. Para o exercício de análise, nos debruçamos sobre as categorizações do Congresso enquanto “conservador”. En 2001, Iara Bernardi, diputada de Partido de los Trabajadores en São Paulo, propuso el Proyecto de Ley de la Cámara 122 (PLC 122), conocido como "ley anti-homofobia", con el objetivo de incluir la discriminación por orientación sexual o identidad de género en el Código Penal, específicamente la Ley 7716, de 1989, conocida como Ley de Racismo). Este artículo presenta un recorte de las conclusiones de mi tesis doctoral, que tuvo como objetivo investigar la cobertura periodística sobre el PLC 122, entre 2001 y 2015, cuando el proyecto fue archivado, con base en la Análisis de Pertenencia Categorial (Membership Categorization Analysis). En primer lugar, el artículo presenta un panorama de los cuatro patrones analíticos evidenciados por el estudio, que engloban las categorizaciones de pertenencia utilizadas en el ámbito de los discursos periodísticos en el período, acerca de los sujetos LGBT, del proyecto de ley en sí, de la práctica homosexual y de las instituciones brasileñas, en que Brasil, el Congreso Nacional y el Estado son categorizados. Para el ejercicio de análisis, nos ocupamos de las categorizaciones del Congreso como "conservador".